Purpurin suppresses atopic dermatitis via TNF-α/IFN-γ-induced inflammation in HaCaT cells. (20th June 2022) - Oh, Jae-Hoon; Kim, Seung-Ho; Kwon, Ok-Kyoung; Kim, Jung-Hee; Oh, Sei-Ryang; Han, Sang-Bae; Park, Ji-Won; Ahn, Kyung-Seop
Objective: We investigated whether purpurin inhibits various pathways of inflammation leading to atopic dermatitis. Introduction: 1, 2, 4-Trihydroxyanthraquinone, commonly called purpurin, is an anthraquinone that is a naturally occurring red/yellow dye. Purpurin is a highly antioxidative anthraquinone and previous studies have reported antibacterial, anti-tumor, and anti-oxidation activities in cells and animals. However, the skin inflammatory inhibition activity mechanism study of purpurin has not been elucidated in vitro. Methods: In this study, we investigated the anti-inflammatory activity of purpurin in HaCaT (human keratinocyte) cell lines stimulated with a mixture of tumor necrosis factor-alpha (TNF-α)/Interferon-gamma (IFN-γ). The inhibitory effect of Purpurin on cytokines (IL-6, IL-8, and IL-1β) and chemokine (TARC, MDC, and RANTES) was confirmed by ELISA and RT-qPCR. We investigated each signaling pathway and the action of inhibitors through western blots. Results: The expression levels of cytokines and chemokines were dose-dependently suppressed by purpurin treatment in TNF-α/IFN-γ-induced HaCaT cells from ELISA and real-time PCR. Purpurin also inhibited protein kinase B (AKT), mitogen-activated protein kinase (MAPKs), and nuclear factor kappa-light-chain-enhancer of activated B (NF-κB) activation in TNF-α/IFN-γ-stimulated HaCaT cells. Additionally, there was a synergistic effect when purpurin and inhibitor were applied together, and inflammation was dramatically reduced. Conclusion: Therefore, these results demonstrate that purpurin exhibits anti-inflammatory and anti-atopic dermatitis activity in HaCaT cells.